Answer:
-1
Step-by-step explanation:
When b<4
|b-4| is negative
|b-4| = - ( b-4)
- (b-4) / ( b-4) =
Factoring out (b-4)
-1
Answer:
130/81
simplified: 1 49/81
Step-by-step explanation:
I did the math
Answer:$96.98
Step-by-step explanation: all you just do is to add it all up to the total amount.
Answer:
A Linear Expression is the correct choice for this equation
Answer:
f⁻¹(x) = x - 3
General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
- Multiplication Property of Equality
- Division Property of Equality
- Addition Property of Equality
- Subtraction Property of Equality<u>
</u>
<u>Algebra I</u>
- Functions
- Function Notation
- Inverse Functions
Step-by-step explanation:
<u>Step 1: Define</u>
<em>Identify</em>
f(x) = x + 3
<u>Step 2: Find</u>
- Swap: x = y + 3
- [Subtraction Property of Equality] Isolate <em>y</em>: x - 3 = y
- Rewrite: f⁻¹(x) = x - 3